Empirical use of plant extracts: Herbal care in medicine and dentistry - Emerenciano Bueno, Carlos Roberto [UNESP] (My University, 2020)
The use of herbs, herbs extracts and medicinal plants incorporated in traditional medicine has a long and ancient history going back centuries in medicine and dental practice around the world to prevent, control or recover health against several diseases. Plants are considered mankind's first medicine, which were used mainly as antiseptics, analgesics, antiinflammatory or with antimicrobial purpose. According to the World Health Organization, near 80% of the populations of developing countries still use medicinal plants as a therapeutic resource. Over the years, many plants scientifically demonstrated biological and antimicrobial properties due to the interactions with specific chemical receptors within the body, becoming promising therapeutic agents. Thus, this chapter introduces historic findings of the use of plant extracts in archaic medicine and dentistry, initially used as medicaments for body and, consequently, oral disease. An initial historic overview will link, along this book, the millennial empirical use of plants and its extracts to actual researches and findings concerning the use of plants extracts in dentistry.
Keywords: Dentistry; Ethnopharmacology; Medicinal Plants; Phytotherapy; Plant Extracts